Coated steel member
By forming a high Fe content oxide layer on the surface of the high-strength steel plate and controlling the depth of the internal oxide layer and carbon removal layer, the problems of fracture and inaccurate size in complex shape manufacturing are solved, and high-precision complex shape molding and excellent welding performance of the high-strength steel plate are achieved.
Patent Information
- Application Number
- JP2025006095
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-17
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-10
AI Technical Summary
High-strength steel plates are prone to break during the manufacturing process of complex shapes, and residual stress after hot pressing leads to inaccurate dimensions, making it difficult to achieve complex shape die-casting of high-strength steel plates.
The high Fe content oxide layer is formed on the surface of the steel plate by hot press forming technology, and the depth of the internal oxide layer and carbon removal layer is controlled within an appropriate range to improve the strength and plasticity of the steel plate.
High-precision and complex shape forming of high-strength steel plates is realized, and the strength, plasticity and welding performance of the steel plates are improved.
Smart Images

Figure 2025061391000011 
Figure 2025061391000012 
Figure 2025061391000013
Abstract
Description
[Technical field]
[0001] The present invention relates to coated steel components. This application claims priority based on Japanese Patent Application No. 2021-043720, filed on March 17, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] In the field of automotive steel sheets, the use of steel sheets with high tensile strength (high-strength steel sheets) is expanding in order to improve both fuel efficiency and crashworthiness against the backdrop of recent stricter environmental regulations and crash safety standards. However, as the strength of steel sheets increases, the press formability of the steel sheets decreases, making it difficult to manufacture products with complex shapes.
[0003] Specifically, as the strength of steel sheets is increased, the ductility of the steel sheets decreases, and when the steel sheets are processed into complex shapes, the steel sheets break at highly processed areas. In addition, as the strength of steel sheets is increased, the residual stress after processing causes springback and wall warping, which deteriorates the dimensional accuracy. Therefore, it is not easy to press-form high-strength steel sheets, especially those with a tensile strength of 780 MPa or more, into products with complex shapes. Although high-strength steel sheets can be easily processed by roll forming instead of press forming, the application of roll forming is limited to parts with a uniform cross section in the longitudinal direction.
[0004] In recent years, therefore, hot stamping technology has been adopted as a technique for press forming difficult-to-form materials such as high-strength steel sheets. Hot stamping technology is a hot forming technology in which the material to be formed is heated and then formed.
[0005] In this technology, the material is heated before it is formed. Therefore, the steel material is soft during forming and has good formability. This allows even high-strength steel plates to be formed into complex shapes with high precision. In addition, in hot stamping technology, the steel material is quenched at the same time as it is formed using a press die, so the steel member has sufficient strength after forming.
[0006] For example, Patent Document 1 discloses that hot stamping technology can impart a tensile strength of 1400 MPa or more to a formed steel member.
[0007] On the other hand, automobiles are also required to have crashworthiness. The crashworthiness of an automobile is evaluated based on the crush strength and absorbed energy in crash tests of the entire body and some of its components. Since the crush strength in particular depends heavily on the strength of the material, the demand for ultra-high strength steel components as automobile components has increased dramatically. However, in general, the fracture toughness and deformability of steel members decrease with increasing strength. Therefore, in the event of a collision, the steel members may break early or at a location where deformation is concentrated, and the crushing strength commensurate with the material strength may not be exhibited, resulting in insufficient absorption of energy. Therefore, in order to improve the collision safety of automobiles, it is necessary to improve not only the material strength of the steel members used, but also the fracture toughness and deformability, that is, the toughness and bendability. Therefore, in order to apply high-strength steel members with a tensile strength of more than 1.0 GPa to the vehicle body, a technology is required to provide steel members that have toughness and bendability higher than conventional steel members and that exhibit sufficient absorption of energy even in the event of a collision accident.
[0008] Patent Document 2 discloses a hot press-formed product having excellent toughness and a tensile strength of 1.8 GPa or more. Patent Document 3 discloses a steel material having an extremely high tensile strength of 2.0 GPa or more, and also having good toughness and ductility. Patent Document 4 discloses a steel material having a high tensile strength of 1.8 GPa or more, and also having good toughness. Patent Document 5 discloses a steel material having an extremely high tensile strength of 2.0 GPa or more, and also having good toughness. However, Patent Documents 1 to 5 are silent about bendability, and may not be able to fully meet the higher demands for use as automobile parts using high-strength steel materials with a tensile strength exceeding 1.0 GPa.
[0009] Furthermore, steel members are usually assembled by welding before being applied to automobile bodies, and therefore, when envisaging their use in automobile parts, they are required to have excellent weldability in addition to the above-mentioned high strength and bendability. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Publication No. 2002-102980 [Patent Document 2] Japanese Patent Application Publication No. 2012-180594 [Patent Document 3] Japanese Patent Publication No. 2012-1802 [Patent Document 4] International Publication No. 2015 / 182596 [Patent Document 5] International Publication No. 2015 / 182591 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in view of the above problems, and an object of the present invention is to provide a coated steel member that has high strength and excellent bendability and weldability. [Means for solving the problem]
[0012] The present inventors have conducted studies to obtain excellent bendability and weldability in a high-strength steel member obtained by hot stamping a steel sheet. As a result, they discovered that by increasing the Fe content of the scale formed on the surface of a steel plate (base steel plate) subjected to hot stamping and controlling the depth (thickness) of the internal oxidation layer and decarburized layer within an appropriate range, the steel component obtained by hot stamping this steel plate can have high strength as well as excellent bendability and weldability.
[0013] The present invention has been made in view of the above problems. [1] A coated steel member according to one aspect of the present invention has a steel sheet substrate and a coating containing Al and Fe formed on a surface of the steel sheet substrate, the steel sheet substrate containing, by mass%, C: 0.10 to 0.65%, Si: 0.10 to 2.00%, Mn: 0.30 to 3.00%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, O: 0.010% or less, Ti: 0 to 0.100%, B: 0 to 0.0100%, Cr: 0 to 1.00%, Mo: 0 to 1.00%, Ni: 0 to 1.00%, Nb: 0 to 0.10%, Cu: 0 to 1.00%, V: 0 to 1.00%, Ca: 0 to 0.010%, Mg: 0 to 0.0 and REM: 0-0.30%, with the balance being Fe and impurities; the steel plate substrate has a decarburized layer formed on the coating side, the decarburized layer has an internal oxide layer formed on the coating side, the depth of the decarburized layer from the interface between the steel plate substrate and the coating is 30 μm or more, the depth of the internal oxide layer from the interface is less than 20 μm, and no scale is present between the steel plate substrate and the coating containing Al and Fe. Effect of the Invention
[0014] According to the above-mentioned aspect of the present invention, it is possible to provide a coated steel member having high strength and excellent bendability and weldability. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a schematic diagram showing an example of a steel plate according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a steel member according to the present embodiment. [Diagram 3] FIG. 2 is a schematic diagram showing an example of another aspect (coated steel member) of the steel member according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, a steel plate according to one embodiment of the present invention (steel plate according to this embodiment) and a steel member (including a coated steel member) (steel member according to this embodiment) and preferable methods for producing them will be described.
[0017] First, the steel plate according to this embodiment will be described. As shown in Fig. 1, the steel plate 10 according to this embodiment has a base steel plate 11 having the chemical composition shown below, and a scale 12 containing 80 mass% or more of Fe formed on the surface of the base steel plate 11. The base steel plate 11 also has a decarburized layer 13 of a predetermined depth on the interface side with the scale 12 (a region in contact with the interface), and the decarburized layer 13 has an internal oxide layer 14 on the interface side between the base steel plate 11 and the scale 12. Although FIG. 1 shows scale on only one side, the scale may be formed on both sides, in which case the decarburized layer 13 and the internal oxidation layer 14 are formed in the regions of the base steel plate 11 that contact the interfaces with the scale on both sides. In this embodiment, "scale side" means "the scale side in the plate thickness direction of the base steel plate", and "the interface side with the scale" means "the interface side between the base steel plate and the scale in the plate thickness direction of the base steel plate (the area in contact with the interface)".
[0018] <Base material steel plate> [Chemical composition] In the following numerical ranges enclosed by "~", the values at both ends are included as the lower and upper limits of the range. However, values indicated as "greater than" or "less than" are not included in the numerical range. "%" regarding the content of each element means "mass%" unless otherwise specified.
[0019] C: 0.10-0.65% C is an element that improves the hardenability of steel and improves the strength of a steel member after hot stamping (obtained by hot stamping a steel sheet). However, if the C content is less than 0.10%, it is difficult to ensure sufficient strength (over 1.0 GPa) in the steel member after hot stamping (steel member obtained by hot stamping a steel sheet). Therefore, the C content is set to 0.10% or more. The C content is preferably 0.15% or more, and more preferably 0.26% or more. On the other hand, if the C content exceeds 0.65%, the strength of the steel member after hot stamping becomes too high, and the bendability deteriorates significantly. In addition, the weldability also deteriorates. Therefore, the C content is set to 0.65% or less. The C content is preferably 0.60% or less.
[0020] Silicon: 0.10 to 2.00% Silicon is an element that is effective in improving the hardenability of steel and in stably ensuring the strength of steel members after hot stamping. To obtain this effect, the silicon content must be 0.10% or more. The silicon content is preferably 0.35% or more. On the other hand, if the Si content in the steel plate exceeds 2.00%, the heating temperature required for austenite transformation during heat treatment becomes significantly high. This may increase the cost required for heat treatment. Furthermore, if the Si content exceeds 2.00%, the toughness of the quenched part deteriorates. Therefore, the Si content is set to 2.00% or less. The Si content is preferably 1.60% or less.
[0021] Mn: 0.30-3.00% Mn is an extremely effective element for improving the hardenability of steel and stably securing the strength of steel members after hot stamping. Mn also lowers the Ac3 point and promotes lowering the quenching temperature. Mn is also an element that has the effect of improving corrosion resistance by diffusing into an Al-Fe coating. If the Mn content is less than 0.30%, these effects are insufficient, so the Mn content is set to 0.30% or more. The Mn content is preferably 0.40% or more. On the other hand, if the Mn content exceeds 3.00%, the above effects are saturated and the toughness and bendability of the hardened portion deteriorate. Therefore, the Mn content is set to 3.00% or less. The Mn content is preferably 2.80% or less, and more preferably 2.50% or less.
[0022] P:0.050% or less P is an element that deteriorates the toughness of steel members after hot stamping. In particular, if the P content exceeds 0.050%, the deterioration of toughness becomes significant. Therefore, the P content is limited to 0.050% or less. The P content is preferably limited to 0.005% or less. Since a small P content is preferable, 0% is acceptable, but from the viewpoint of cost, it may be 0.001% or more.
[0023] S: 0.0100% or less S is an element that deteriorates the toughness and bendability of steel members after hot stamping. In particular, when the S content exceeds 0.0100%, the deterioration of toughness and bendability becomes significant. Therefore, the S content is limited to 0.0100% or less. The S content is preferably limited to 0.0050% or less. Since a small S content is preferable, 0% is acceptable, but from the viewpoint of cost, it may be 0.0001% or more.
[0024] N: 0.010% or less N is an element that deteriorates the toughness of steel members after hot stamping. In particular, if the N content exceeds 0.010%, coarse nitrides are formed in the steel, and the toughness is significantly deteriorated. Therefore, the N content is set to 0.010% or less. There is no need to particularly limit the lower limit of the N content, and it may be 0%, but setting the N content to less than 0.0002% increases the steelmaking cost and is economically undesirable. Therefore, the N content may be set to 0.0002% or more, or 0.0008% or more.
[0025] O: 0.010% or less O is an element that deteriorates the toughness of a steel member after hot stamping. In particular, if the O content exceeds 0.010%, coarse oxides are formed in the steel, and the toughness is significantly deteriorated. Therefore, the O content is set to 0.010% or less. There is no need to particularly limit the lower limit of the O content, and it may be 0%, but setting the O content to less than 0.0002% increases the steelmaking cost and is economically undesirable. Therefore, the O content may be set to 0.0002% or more, or 0.0008% or more.
[0026] In order to improve strength, toughness, bendability, corrosion resistance, and deoxidization, the steel member according to this embodiment may further contain, in addition to the above elements, one or more elements selected from Ti, B, Cr, Mo, Ni, Nb, Cu, V, Ca, Mg, Al, Sn, W, Sb, Zr, Co, and REM shown below. These elements are optional elements and do not necessarily need to be contained, so the lower limit is 0%.
[0027] Ti: 0 to 0.100% Ti is an element that suppresses recrystallization when a steel sheet is heated to a temperature of the Ac3 point or higher and subjected to heat treatment, and also forms fine carbides to suppress grain growth, thereby making austenite grains finer. Therefore, by including Ti, the effect of greatly improving the toughness of the steel member after hot stamping can be obtained. In addition, Ti is an element that suppresses the consumption of B due to the precipitation of BN by preferentially bonding with N in the steel, and promotes the effect of improving hardenability by B, which will be described later. Therefore, Ti may be included. To obtain the above effects sufficiently, the Ti content is preferably 0.010% or more. The Ti content is more preferably 0.020% or more. On the other hand, if the Ti content exceeds 0.100%, the amount of TiC precipitated increases and C is consumed, resulting in a decrease in the strength of the steel member after hot stamping. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably 0.080% or less.
[0028] B: 0~0.0100% B is an element that has the effect of dramatically improving the hardenability of steel even in a small amount. In addition, B is an element that segregates at grain boundaries to strengthen the grain boundaries and increase toughness, and is an element that suppresses the grain growth of austenite when the steel sheet is heated. Therefore, B may be contained. To fully obtain the above effects, the B content is preferably 0.0010% or more. The B content is more preferably 0.0020% or more. On the other hand, if the B content exceeds 0.0100%, a large amount of coarse compounds precipitates, and the toughness of the steel member after hot stamping deteriorates. Therefore, if B is contained, the B content is set to 0.0100% or less. The B content is preferably 0.0080% or less.
[0029] Cr: 0~1.00% Cr is an effective element for improving the hardenability of steel and stably securing the strength of the steel member after hot stamping. Therefore, Cr may be contained. To obtain the above effects, the Cr content is preferably 0.01% or more. The Cr content is more preferably 0.05% or more, and further preferably 0.08% or more. On the other hand, if the Cr content exceeds 1.00%, the above effects are saturated and the cost increases. In addition, since Cr has the effect of stabilizing iron carbides, if the Cr content exceeds 1.00%, coarse iron carbides may remain unmelted when the steel plate is heated, which may deteriorate the toughness of the steel member after hot stamping. Therefore, if Cr is contained, the Cr content is set to 1.00% or less. The Cr content is preferably 0.80% or less.
[0030] Mo: 0 to 1.00% Mo is an effective element for improving the hardenability of steel and stably securing the strength of the steel member after hot stamping. Therefore, Mo may be contained. To obtain the above effects, the Mo content is preferably 0.01% or more. The Mo content is more preferably 0.05% or more. On the other hand, if the Mo content exceeds 1.00%, the above effects are saturated and the cost increases. In addition, since Mo has the effect of stabilizing iron carbides, if the Mo content exceeds 1.00%, coarse iron carbides may remain unmelted during heating of the steel plate, which may deteriorate the toughness of the steel member after hot stamping. Therefore, if Mo is contained, the Mo content is set to 1.00% or less. The Mo content is preferably 0.80% or less.
[0031] Ni: 0 to 1.00% Ni is an effective element for improving the hardenability of steel and for stably securing the strength of the steel member after hot stamping. Therefore, Ni may be contained. To obtain the above effects, the Ni content is preferably 0.01% or more. The Ni content is more preferably 0.10% or more. On the other hand, if the Ni content exceeds 1.00%, the above effects become saturated and the economic efficiency decreases. Therefore, if Ni is contained, the Ni content is set to 1.00% or less.
[0032] Nb: 0 to 0.10% Nb is an element that forms fine carbides and has the effect of increasing the toughness of steel by its grain refining effect. Therefore, Nb may be contained. To obtain the above effect sufficiently, the Nb content is preferably 0.02% or more. The Nb content is more preferably 0.03% or more. On the other hand, if the Nb content exceeds 0.10%, the carbides become coarse and the toughness of the steel member deteriorates. Therefore, the Nb content is set to 0.10% or less. The Nb content is preferably 0.08% or less.
[0033] Cu: 0-1.00% Cu is an element effective for improving the hardenability of steel and stably ensuring the strength of the steel member after hot stamping. Therefore, Cu may be contained. Cu is also an element that has the effect of improving the corrosion resistance of the steel member. To obtain the above effect, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.05% or more. On the other hand, if the Cr content exceeds 1.00%, the above effects are saturated and the cost increases. Therefore, if Cu is contained, the Cu content is set to 1.00% or less. The Cu content is preferably 0.80% or less.
[0034] V: 0~1.00% V is an element that forms fine carbides and enhances the toughness of steel by its grain refining effect. Therefore, V may be contained. To obtain the above effect, the V content is preferably 0.01% or more. The V content is more preferably 0.10% or more. On the other hand, if the V content exceeds 1.00%, the above effects become saturated and the economic efficiency decreases. Therefore, if V is contained, the V content is set to 1.00% or less.
[0035] Ca: 0 to 0.010% Ca is an element that has the effect of refining inclusions in steel and improving toughness after hot stamping. Therefore, Ca may be contained. To obtain the above effect, the Ca content is preferably 0.001% or more. The Ca content is more preferably 0.002% or more. On the other hand, if the Ca content exceeds 0.010%, the effect is saturated and the cost increases. Therefore, if Ca is contained, the Ca content is set to 0.010% or less. The Ca content is preferably 0.005% or less, and more preferably 0.004% or less.
[0036] Magnesium: 0 to 0.010% Mg is an element that has the effect of refining inclusions in steel and improving the toughness of the steel member after hot stamping. Therefore, Mg may be contained. To obtain the above effect, the Mg content is preferably 0.001% or more. The Mg content is more preferably 0.002% or more. On the other hand, if the Mg content exceeds 0.010%, the effect saturates and the cost increases. Therefore, if Mg is contained, the Mg content is set to 0.010% or less. The Mg content is preferably 0.005% or less, and more preferably 0.004% or less.
[0037] Al: 0-1.00% Al is an element that is generally used as a deoxidizer for steel. Therefore, Al may be contained. In order to obtain the above effects, the Al content is preferably 0.01% or more. On the other hand, if the Al content exceeds 1.00%, the above effects become saturated and the economic efficiency decreases. Therefore, if Al is contained, the Al content is set to 1.00% or less.
[0038] Sn: 0 to 1.00% Sn is an element that improves corrosion resistance in a corrosive environment. Therefore, Sn may be contained. In order to obtain the above effects, the Sn content is preferably 0.01% or more. On the other hand, if the Sn content exceeds 1.00%, the grain boundary strength decreases, and the toughness of the steel member after hot stamping deteriorates. Therefore, if Sn is contained, the Sn content is set to 1.00% or less.
[0039] W: 0~1.00% W is an element that enhances the hardenability of steel and enables the strength of the steel member after hot stamping to be stably ensured. Therefore, W may be contained. W is also an element that improves corrosion resistance in a corrosive environment. To obtain the above effects, the W content is preferably 0.01% or more. On the other hand, if the W content exceeds 1.00%, the above effects become saturated and the economic efficiency decreases. Therefore, if W is contained, the W content is set to 1.00% or less.
[0040] Sb: 0 to 1.00% Sb is an element that improves corrosion resistance in a corrosive environment. Therefore, Sb may be contained. In order to obtain the above effects, the Sb content is preferably 0.01% or more. However, if the Sb content exceeds 1.00%, the grain boundary strength decreases, and the toughness of the steel member after hot stamping deteriorates. Therefore, if Sb is contained, the Sb content is set to 1.00% or less.
[0041] Zr: 0 to 1.00% Zr is an element that improves corrosion resistance in a corrosive environment. Therefore, Zr may be contained. In order to obtain the above effects, the Zr content is preferably 0.01% or more. On the other hand, if the Zr content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel member after hot stamping decreases. Therefore, if Zr is contained, the Zr content is set to 1.00% or less.
[0042] Co: 0 to 1.00% Co is an element that improves corrosion resistance in a corrosive environment, and therefore Co may be contained. In order to obtain the above effects, the Co content is preferably 0.01% or more. On the other hand, if the Co content exceeds 1.00%, the above effects become saturated and the economic efficiency decreases. Therefore, if Co is contained, the Co content is set to 1.00% or less.
[0043] REM: 0~0.30% Like Ca, REM is an element that has the effect of refining inclusions in steel and improving the toughness of the steel member after hot stamping. Therefore, REM may be contained. To obtain the above effect, the REM content is preferably 0.01% or more. The REM content is more preferably 0.02% or more. On the other hand, if the REM content exceeds 0.30%, the effect saturates and the cost increases. Therefore, if REM is contained, the REM content is set to 0.30% or less. The REM content is preferably 0.20% or less.
[0044] Here, REM refers to a total of 17 elements including Sc, Y, and lanthanides such as La and Nd, and the content of REM means the total content of these elements. REM is added to molten steel using, for example, an Fe-Si-REM alloy, and this alloy contains, for example, La, Nd, Ce, and Pr.
[0045] In the chemical composition of the base steel plate of the steel plate according to this embodiment, the elements other than those described above, that is, the balance, are Fe and impurities. Here, "impurities" refer to components that are mixed in due to various factors in raw materials such as ores and scraps and the manufacturing process when industrially producing steel plate, and are acceptable within a range that does not adversely affect the properties of the steel plate and the steel member according to this embodiment.
[0046] The chemical composition of the base steel sheet can be determined by the following method. The value can be obtained by cutting an analysis sample from the base steel plate and performing elemental analysis such as ICP (inductively coupled plasma) atomic emission spectrometry. C and S can be measured using the combustion-infrared absorption method, N can be measured using the inert gas fusion-thermal conductivity method, and O can be measured using the inert gas fusion-non-dispersive infrared absorption method. The analytical sample is taken so as to obtain the average chemical composition throughout the thickness of the base steel plate as described in JIS G 0417: 1999. Specifically, the analytical sample is taken from a position 1 / 4 of the plate thickness from the surface in the plate thickness direction, avoiding the ends in the width direction of the base steel plate.
[0047] [Decarburized layer] [Internal oxidation layer] As shown in FIG. 1, the base steel plate 11 of the steel plate 10 according to this embodiment has a decarburized layer 13 on the scale 12 side (the interface side between the base steel plate 11 and the scale 12). That is, a part of the scale 12 side of the base steel plate 11 is the decarburized layer 13. The decarburized layer 13 also has an internal oxidation layer 14 on the scale 12 side. That is, a part of the decarburized layer 13 on the scale 12 side is the internal oxidation layer 14. The depth of the internal oxidation layer 14 from the interface between the base steel plate 11 and the scale 12 in the cross section in the thickness direction (the distance in the thickness direction from the interface) is less than 30 μm. The depth of the decarburized layer 13 from the interface between the base steel plate 11 and the scale 12 in the cross section in the thickness direction (the distance in the thickness direction from the interface) is 90 μm or more. In steel members obtained by hot stamping a steel sheet, it is extremely effective to decarburize and soften the surface layer in order to improve the bendability. Since bending deformation generates larger stress and strain in the surface layer outside the bend, softening the surface layer and improving the fracture limit can improve the bendability. In the steel plate 10 according to the present embodiment, in order to form a decarburized layer on the surface layer of the steel member after hot stamping, a decarburized layer 13 is formed on the interface side of the base steel plate 11 with the scale 12 described later, with a depth (thickness) of 90 μm or more from the interface. If the depth (thickness) of the decarburized layer 13 is less than 90 μm, the decarburized layer is not formed to a sufficient depth in the steel plate base material of the steel member after hot stamping, and the bendability of the steel member is reduced. Although the surface of the base steel plate is recarburized by hot stamping and the decarburized layer depth becomes smaller, by making the decarburized layer depth of the base steel plate 11 90 μm or more, the decarburized layer depth of the steel member after hot stamping can be made 60 μm or more under normal hot stamping conditions.
[0048] As described above, a method (high dew point annealing) is known as a technique for decarburizing the surface layer of a steel sheet, in which the steel sheet is annealed at a high dew point and decarburized with H2O in the atmosphere. However, as a result of the studies by the present inventors, it was found that when such high dew point annealing is performed, internal oxidation (oxidation of easily oxidizable elements such as Si and Mn in steel) that occurs simultaneously with decarburization causes various problems. Specifically, it was found that in a steel member obtained by hot stamping, scale (internal scale) is generated inside the steel sheet starting from the internal oxide layer during hot stamping, and the scale generated from inside the steel sheet may inhibit weldability. As a result of further investigations, the inventors have found that in a steel sheet (base steel sheet 11) to be subjected to hot stamping, the generation of scale inside the steel sheet during hot stamping can be suppressed by making the depth of the internal oxide layer 14 less than 30 μm. Therefore, in the steel sheet 10 according to this embodiment, the depth (thickness) of the internal oxide layer 14 of the base steel sheet 11 from the interface between the base steel sheet 11 and the scale 12 is made less than 30 μm. The depth of the internal oxide layer is preferably less than 5 μm, in which case the bendability becomes more advantageous. In order to restrict the depth of the internal oxide layer 14 while ensuring the depth of the decarburized layer 13, it is necessary to control the annealing conditions as described later.
[0049] In addition, it is preferable that the ratio of the depth (thickness) of the decarburized layer to the depth (thickness) of the internal oxide layer is 3 or more ( / thickness of the internal oxide layer ≧ 3). In this case, the bendability described below becomes more superior. More preferably, the above ratio is 10 or more. Further preferably, the above ratio is 20 or more.
[0050] The depth of the decarburized layer 13 from the interface between the base steel sheet 11 and the scale 12 can be determined by the following method using GDS. GDS (glow discharge optical emission spectrometry) is performed from the surface of the steel sheet in the sheet thickness direction to determine the depth of the decarburized layer. The GDS measurement is performed at a position of 1 / 4 of the sheet width (short side) from the end of the width direction of the steel sheet, and the C content and Fe content are measured from the surface (surface of the scale) toward the sheet thickness direction at a pitch of 50 nm or less. The position where the Fe content becomes 95% or more for the first time as a result of the measurement is defined as the interface between the base steel sheet and the scale. The position where the C content obtained by the GDS analysis is the C content at the position of 1 / 4 of the sheet thickness from the surface of the base steel sheet described above is defined as the deepest position of the decarburized layer. The distance from the interface between the base steel sheet and the scale to the deepest position of the decarburized layer is defined as the depth of the decarburized layer from the interface between the base steel sheet and the scale (thickness of the decarburized layer). However, the above measurement is performed five times at different positions, and the average value of the five measurements is defined as the depth of the decarburized layer from the interface between the base steel sheet and the scale of the steel sheet according to this embodiment (also referred to as the total decarburization depth). If the decarburized layer is deep enough to exceed the measurement limit of GDS, the depth of the decarburized layer may be determined by microscopic observation as described in JIS G 0558 (2007). In this case, a sample for cross-sectional observation is taken from the end of the width direction of the steel plate at a position 1 / 4 of the plate width (short side) in the width direction, and this sample is etched with nital and the cross-section is observed using an optical microscope. The depth at which the structure is equivalent to the position 1 / 4 of the plate thickness from the surface (interface with the scale) of the base steel plate is measured, and the depth at that position is taken as the depth of the decarburized layer. However, the measurement is performed five times at different locations, and the average of the five measurements is taken as the decarburized layer depth.
[0051] The depth of the internal oxide layer from the interface between the base steel sheet and the scale is determined by observing the cross section of the steel sheet with a SEM (scanning electron microscope). A sample for cross-sectional observation is taken from a position 1 / 4 of the sheet width (short side) from the width direction end of the steel sheet, and a COMPO image is observed by SEM. Since internal oxidation progresses deeper at the grain boundaries than within the grains and appears darker in the COMPO image than the steady part of the base steel sheet (high Fe content), the internal oxide layer is identified based on the difference in color, and the depth of the deepest internal oxide layer from the interface between the base steel sheet and the scale is measured. However, the above measurement is performed five times at different locations, and the average value of the five measurements is regarded as the depth from the interface with the internal oxide layer scale of the steel sheet according to this embodiment.
[0052] [scale] The steel sheet according to this embodiment has a scale formed on the surface of the base steel sheet. As described later, the steel sheet according to this embodiment decarburizes the base steel sheet by utilizing O in the scale formed on the surface of the base steel sheet by rolling or the like. Therefore, the scale after decarburization has a significantly reduced O content compared to normal scale consisting of FeO, Fe2O3, Fe3O4, etc. that is usually formed by hot rolling or the like, and contains 80% or more Fe by mass%. That is, by carrying out decarburization under conditions in which the Fe content of the scale is 80% or more, it is possible to obtain a steel sheet having an internal oxide layer and a decarburized layer of the above-mentioned depth. In other words, scale may be removed or peeled off from a steel plate during processing or the like, but a steel plate having an internal oxidation layer and a decarburized layer with depths within the above-mentioned ranges can also be considered to have had scale equivalent to that of the steel plate according to this embodiment. From the viewpoint of supplying O for decarburization, the thickness of the scale is preferably 5 μm or more, more preferably 8 μm or more, and further preferably 10 μm or more. From the viewpoint of the yield of the steel sheet, the thickness of the scale is preferably less than 100 μm, and more preferably 50 μm or less, or 30 μm or less.
[0053] The scale provided on the steel plate according to the present embodiment preferably includes, in mass%, a first region containing 80% or more Fe and 0.1% or more but less than 3.0% Si, and a second region containing 65% or more but less than 80% Fe and 0.8% or more but less than 7.5% Mn. It is preferable that the scale essentially consists of the first region and the second region. However, the scale may contain, as "other regions", impurities or oxides mainly composed of Cr, Si, etc., or simple substances of difficult-to-oxidize elements such as Cu, etc., in the outermost layer. By using a scale having such a configuration, it is possible to improve the current limit at which flash occurs during spot welding when assembling a vehicle body, and to obtain a steel plate with a wide appropriate current range, i.e., with good weldability. The first region may contain C, Ni, Cr, Mo, etc. in addition to Fe, Si, and O. The second region may contain C, Ni, etc. in addition to Fe, Mn, and O.
[0054] When the first and second regions exist, the second region is often present in an island-like form in the first region, which is a matrix. The second region may be dispersed in islands, or may be formed by combining several islands. In either case, the first and second regions can be distinguished from each other by the method described below.
[0055] The Fe content of the scale is determined by the following method. GDS (glow discharge optical emission spectrometry) is performed from the surface in the thickness direction at a position 1 / 4 of the sheet width (short side) from the width direction end of the steel sheet, and the Fe content and O content of the scale are determined. Areas with an O content of 0.1% or more are excluded as impurities, and the average Fe content is measured in areas from the surface where the O content is less than 0.1%. The measurement is performed five times at different locations, and the average of the five measurements is taken as the Fe content of the scale. The Fe content and Si content in the first region of the scale, and the Fe content and Mn content in the second region are determined using a SEM (electron scanning electron microscope) and an electron probe microanalyzer (EPMA). A sample is taken from a position 1 / 4 of the sheet width (short side) from the end of the width direction of the steel sheet so that the cross section of the steel sheet in the sheet thickness direction can be observed. A COMPO image is obtained from this sample using a scanning electron microscope to confirm the presence of two types of textures with different contrasts that make up the scale. The first region contains more Fe, a heavy element, than the second region, so it appears brighter than the second region. Therefore, the relatively bright region is defined as the first region, and the relatively dark region is defined as the second region. For each of these two types of textures (first region and second region), an electron probe microanalyzer (EPMA) is used to perform spot elemental analysis (beam diameter 1 μm or less) to determine the Fe content and Si content contained in the first region of the scale and the Fe content and Mn content contained in the second region. When measuring, 10 points are analyzed for each, and the average values are taken as the Fe and Si contents in the first region of the scale and the Fe and Mn contents in the second region. The scale may also contain "other regions" as described above. Regions containing 10 mass% or more of Cr, Si, or Cu are considered to be the above-mentioned "other regions."
[0056] The thickness of the scale is measured using an SEM. A sample for cross-sectional observation is taken from the end of the steel plate in the width direction, at a position 1 / 4 of the plate width (short side), and a COMPO image is observed using an SEM. The scale thickness is measured at 10 points where the scale has not peeled off, and the average value is taken as the scale thickness.
[0057] <Steel parts> 2, a steel member 110 according to this embodiment has a steel plate substrate 111 having a predetermined chemical composition, and a scale 112 containing 70 mass % or more of Fe and formed on the surface of the steel plate substrate 111. The steel plate substrate 111 also has a decarburized layer 113 of a predetermined depth formed on the scale 112 side (the interface side with the scale 112), and this decarburized layer 113 has an internal oxide layer 114 formed on the scale 112 side. Moreover, the steel member 110 according to this embodiment is obtained by subjecting the above-described steel plate 10 according to this embodiment to heat treatment (and processing) such as hot stamping. In the drawing, the steel member 110 according to this embodiment is shown in the form of a flat plate, but it is a member obtained by hot stamping, and is not limited to a flat plate.
[0058] [Chemical composition] Since the chemical composition of the steel plate does not substantially change due to hot stamping, the chemical composition of the steel plate substrate 111 of the steel member 110 in this embodiment is the same as the chemical composition of the base steel plate 11 of the steel plate 10 in this embodiment, and can be measured using the same measurement method as for the base steel plate.
[0059] [Decarburized layer] [Internal oxidation layer] In the steel member 110 according to this embodiment, a decarburized layer exists at the interface side of the steel plate substrate 111 with the scale 112, and an internal oxidation layer 114 exists at the interface side of the decarburized layer 113 with the scale 112. Furthermore, the depth of the decarburized layer 113 from the interface between the steel plate substrate 111 and the scale 112 is 60 μm or more, and the depth of the internal oxidation layer 114 from the interface between the steel plate substrate 111 and the scale 112 is less than 40 μm. In steel members, decarburizing and softening the surface layer is extremely effective in improving the bendability. Since bending deformation generates greater stress and strain in the surface layer outside the bend, softening the surface layer and improving the fracture limit can improve the bendability. If the depth (thickness) of the decarburized layer 113 formed on the surface layer of the steel member 110 according to this embodiment is 60 μm or more, the bendability is improved. Therefore, the depth of the decarburized layer 113 from the interface between the steel plate substrate 111 and the scale 112 is set to 60 μm or more. Furthermore, in steel members, if the depth of the internal oxide layer is 40 μm or more, the weldability is reduced due to the scale generated inside the steel sheet during hot stamping, so the depth of the internal oxide layer 114 is set to less than 40 μm.
[0060] <Scale> The steel member 110 according to this embodiment has a scale 112 formed on the surface of a steel plate substrate 111. The steel member 110 according to this embodiment is obtained by hot stamping a steel plate having a scale containing 80% by mass or more of Fe. Although oxidation of the surface layer of the scale progresses due to hot stamping, the scale 112 of the steel member 110 according to this embodiment contains 70% by mass or more of Fe.
[0061] A steel member according to another embodiment of the present invention may be a coated steel member obtained by subjecting the steel sheet according to the present embodiment described above to pickling or the like to remove surface scale, and then forming an Al-containing coating such as plating to form a coated steel sheet, and then subjecting this coated steel sheet to a heat treatment such as hot stamping. In this case, as shown in FIG. 3, a steel member (coated steel member) 210 according to another embodiment of the present invention has a steel plate substrate 211 and a coating 215 containing Al and Fe formed on the surface of the steel plate substrate 211, and does not contain scale between the steel plate substrate 211 and the coating 215 containing Al and Fe. In addition, the steel plate substrate 211 has a decarburized layer 213 formed on the coating 215 side, and the decarburized layer 213 has an internal oxidation layer 214 formed on the coating 215 side, the depth of the decarburized layer 213 from the interface between the steel plate substrate 211 and the coating 215 is 30 μm or more, and the depth of the internal oxidation layer 214 from the interface between the steel plate substrate 211 and the coating 215 is less than 20 μm. If the depth (thickness) of the decarburized layer 213 is 30 μm or more, the bendability is improved. If the depth of the internal oxide layer 214 is less than 20 μm, the weldability is improved. In the case of coated steel members having a coating, the surface oxidation state during heat treatment such as hot stamping differs from that of the above-mentioned steel members having no coating, and therefore the depth of the decarburized layer and the depth of the internal oxide layer differ.
[0062] <Manufacturing method> The steel plate according to this embodiment and the steel member according to this embodiment can be effective as long as they have the above-mentioned characteristics, regardless of the manufacturing method. However, a manufacturing method including the steps shown below (steel plate: (I) to (IV), steel members: (I) to (V)) is preferable because they can be stably manufactured. (I) A process for producing steel billets having a specified chemical composition. (II) A hot rolling step of heating and hot rolling the steel slab to obtain a hot-rolled steel sheet. (III) A winding step of winding the hot-rolled steel sheet into a hot-rolled coil. (IV) An annealing step of box annealing (BAF) the hot-rolled coil on which the hot-rolled scale has been formed. (V) a heat treatment step of cutting out a blank of a predetermined size from the hot rolled coil after the annealing step, and performing heat treatment to obtain a steel member. Each step will be described below. Steps and conditions not described below can be carried out by known methods as appropriate.
[0063] (I) Steel billet manufacturing process In the steel slab production process, steel slabs such as slabs having the above-mentioned preferred chemical composition are produced. Molten steel adjusted to a predetermined chemical composition under known conditions may be cast into steel slabs by continuous casting or the like.
[0064] (II) Hot rolling process In the hot rolling process, the obtained steel slab is heated and hot rolled to produce a hot-rolled steel sheet. In the hot rolling process, scale (hot rolling scale) is formed on the surface of the steel sheet. The hot rolling conditions are not particularly limited, and may be appropriately set within known condition ranges depending on the required properties of the steel sheet.
[0065] (III) Winding process In the coiling process, the hot-rolled steel sheet obtained in the hot rolling process is coiled into a hot-rolled coil. The conditions such as the winding temperature are not particularly limited.
[0066] (IV) Annealing process In the annealing process, the hot-rolled coil, on whose surface hot-rolled scale has formed, is subjected to box annealing (BAF) without removing the scale (in a so-called black scale state). In the annealing, the annealing atmosphere is an inert gas atmosphere (N2 atmosphere, H2 atmosphere, etc.), and the annealing is performed at 650 to 900°C for 4 to 16 hours. In normal decarburization annealing, high dew point annealing is performed, and H2O in the atmosphere is used as the decarburization source. In contrast, in this embodiment, annealing is performed on a hot-rolled coil with hot-rolled scale, and decarburization is performed using O in the scale as the decarburization source. Specifically, C in the outermost layer of the base steel sheet reacts with O in the scale to become CO gas, causing decarburization. Subsequently, the insufficient C is supplied from the inside of the base steel sheet to the outermost layer, and the C becomes CO gas, further advancing the decarburization reaction. At this time, O in the scale is consumed, and the Fe content in the scale increases. However, if the annealing temperature is less than 650°C or the annealing time is less than 4 hours, decarburization does not proceed sufficiently. On the other hand, if the annealing temperature is more than 900°C or the annealing time is more than 16 hours, the reduction reaction of the scale is completed, and the supply of C from the inside of the steel sheet to the surface layer continues, resulting in shallow decarburization. In addition, if the generated CO gas remains around the scale, the decarburization reaction does not proceed further, and a deep decarburized layer cannot be obtained. Therefore, in the manufacturing method of the steel sheet according to this embodiment, it is important to move the gas in the annealing furnace so that the generated CO gas does not remain around the scale. Specifically, a fan or the like is installed in the annealing furnace, and the air volume is set to 250 m 3 By setting the air flow rate at 250 m / Hr or more, the flow rate in the annealing furnace can be secured and the decarburization reaction can be promoted. 3 At less than 1 / Hr, the retention of CO gas around the scale cannot be sufficiently suppressed, resulting in insufficient decarburization. The air volume is the air volume around the hot-rolled coil, and multiple fans or the like may be installed according to the size of the annealing furnace to obtain a specified air volume. The size of the hot-rolled coil is preferably 9 mm or less in thickness, 2100 mm or less in width, 2000 mm or less in outer diameter, and 30 tons or less in weight per coil. Compared to when HO in the atmosphere is used as the decarburization source during high dew point annealing, when O in the scale is used as the decarburization source, the decarburization source O is less likely to penetrate into the inside of the base steel sheet, and as a result, internal oxidation is less likely to progress. In other words, as described above, the hot-rolled coil in the black skin state was subjected to an inert gas atmosphere with a wind volume of 250 m 3 / Hr or more, the desired decarburized layer depth, internal oxide layer depth, and Fe content in the scale described in the steel sheet according to this embodiment can be obtained.
[0067] (V) Heat treatment process In the heat treatment process, a blank of a predetermined size is cut out from the hot rolled coil after the annealing process, and the blank is subjected to heat treatment to form a steel member. The heat treatment is preferably carried out under conditions of heating from the Ac3 point to (Ac3 point + 300) °C at an average heating rate of 1.0 to 1000 °C / sec, and cooling to the Ms point (°C) or below at an average cooling rate equal to or higher than the upper critical cooling rate. A heating rate of less than 1.0° C. / sec is undesirable because it reduces the productivity of the heat treatment, whereas a heating rate of more than 1000° C. / sec is undesirable because it results in a duplex structure and reduces the limit hydrogen content. Furthermore, if the heat treatment temperature is less than the Ac3 point (°C), ferrite will remain after cooling, lowering the strength, which is undesirable, whereas if the heat treatment temperature is more than the Ac3 point + 300°C, the structure will become coarse-grained and the limit hydrogen content will decrease, which is undesirable. The upper critical cooling rate is the minimum cooling rate at which austenite is supercooled to form martensite without precipitating ferrite or pearlite in the structure. If cooling is performed at an average cooling rate below the upper critical cooling rate, ferrite and pearlite will form, resulting in insufficient strength. During heating, the temperature may be held within a range of ±10° C. of the heating temperature for 1 to 300 seconds. After cooling to a temperature equal to or lower than the Ms point, the steel material may be subjected to a tempering treatment in a temperature range of about 100 to 600° C. in order to adjust the strength of the steel material. This heat treatment may be performed simultaneously with processing, i.e., so-called hot stamping may be performed. Furthermore, the steel member (including the coated steel member) according to this embodiment may be a steel member having regions with different strengths, obtained by subjecting a part of a steel plate material to hot forming or heat treatment.
[0068] (VI) Pickling, cold rolling, and coating When the steel member is a coated steel member, the hot-rolled coil may be pickled and cold-rolled between the annealing step and the heat treatment step, and further an Al-containing coating may be formed on the surface. In this case, pickling, cold rolling and coating may be performed under known conditions. If the scale is not sufficiently removed during pickling, shot blasting may be performed before pickling to mechanically promote scale removal. Shot blasting with a grain size of, for example, #60 may be used. EXAMPLES
[0069] First, steel having the chemical composition shown in Table 1 was melted to obtain a slab for hot rolling.
[0070] <Example 1> The obtained slab was subjected to hot rolling to obtain a hot-rolled steel sheet having a thickness of 3.2 mm and a width of 1000 mm, and this hot-rolled steel sheet was wound at a temperature of 800°C or less to obtain a hot-rolled coil having an outer diameter of 1700 mm and a weight of 14 tons per coil. The obtained hot rolled coil was subjected to box annealing under the conditions (temperature, time, air volume) described in Tables 2-1 to 2-3. The annealing atmosphere was a nitrogen atmosphere.
[0071] [Table 1]
[0072] [Table 2-1]
[0073] [Table 2-2]
[0074] [Table 2-3]
[0075] Steel sheets (blanks) of a predetermined size were cut out from the obtained hot-rolled coil after annealing, and GDS (glow discharge optical emission spectroscopy), SEM observation, EPMA analysis, and optical microscope observation were performed as described above to evaluate the decarburized layer depth, internal oxide layer depth, scale thickness, and Fe content of the scale. In addition, the Fe content and Si content in the first region constituting the scale, and the Fe content and Mn content in the second region were evaluated as described above. The evaluation results are shown in Tables 2-1 to 2-3. In addition, the chemical composition of the steel plate at a position 1 / 4 of the plate thickness from the surface was the same as that of the slab.
[0076] As shown in Tables 2-1 to 2-3, in Examples B1 to B60, which satisfy the range of the present invention, steel sheets having the specified chemical composition and structure were obtained. On the other hand, in Comparative Examples b1 to b23, which do not satisfy the range of the present invention, at least one of the desired structures was not satisfied. For example, the first region was not observed in Examples b7 to b19.
[0077] <Example 2> The steel plates shown in Tables 2-1 to 2-3 above were subjected to heat treatment under the conditions shown in Tables 3-1 to 3-3 to obtain steel members.
[0078] The obtained steel members were cut out and GDS (glow discharge optical emission spectrometry), SEM observation, and optical microscope observation were performed as described above to determine the decarburized layer depth, internal oxide layer depth, and Fe content of the scale. The results are shown in Tables 3-1 to 3-3.
[0079] Further, the obtained steel members were subjected to a tensile test, a bending test, and a spot welding test by the following methods, and the tensile strength, bendability, and weldability (proper welding current range) were evaluated.
[0080] <Tensile strength> The tensile tests were carried out in accordance with the provisions of ASTM standard E8. After grinding the soaked portion of the steel member to a thickness of 1.2 mm, a half-size plate test piece (parallel portion length: 32 mm, parallel portion plate width: 6.25 mm) according to ASTM standard E8 was taken so that the test direction was parallel to the rolling direction. A room temperature tensile test was then performed at a strain rate of 3 mm / min to measure the tensile strength (maximum strength). In this example, a tensile strength exceeding 1000 MPa was evaluated as being high strength.
[0081] <Bending property> The bending test was carried out in accordance with the VDA238-100 standard. A bending test piece of 60 mm parallel to the rolling direction and 30 mm perpendicular was taken from the soaked portion of the steel member. The bending punch was aligned perpendicular to the rolling direction, and the bending angle at the maximum load was measured. Since the bending angle correlates with strength, in this example, a bending angle of 55 degrees when the tensile strength is less than 2100 MPa, and a bending angle of more than 45 degrees when the tensile strength is 2100 MPa or more were evaluated as having superior bendability to the conventional technology.
[0082] <Appropriate current range> Spot welding was performed in accordance with JIS Z 3001-6:2013. A single-phase AC 60Hz power source was used, electrodes with a tip diameter of 8mm were used, and the welding time was 10 cycles. Test pieces for spot welding, 40mm in the rolling direction and 30mm vertically, were taken from the soaked heat area of the steel components. These were then glued together, and the range of welding current from when the nugget diameter was 3√t to the upper limit of current at which no expulsion occurred was determined to determine the optimum current range. The nugget diameter was determined as the peel diameter obtained by a peel test. Five welded test pieces were taken for each current, and the average value of the peel diameters was determined as the nugget diameter. If the appropriate current range is 2.5 kA or more, it is determined that the weldability is excellent.
[0083] [Table 3-1]
[0084] [Table 3-2]
[0085] [Table 3-3]
[0086] As shown in Tables 3-1 to 3-3, invention examples C1 to C60, which satisfy the range of the present invention, showed good results in both structure and properties, while comparison examples c1 to c19, which do not satisfy the range of the present invention, did not satisfy the target in at least one of the structure and properties.
[0087] <Example 3> The steel sheets shown in Tables 2-1 to 2-3 above were subjected to pickling, cold rolling, and hot-dip aluminization to obtain coated steel sheets having a thickness of 2.0 mm. The coated steel sheets were subjected to heat treatment under the conditions shown in Tables 4-1 to 4-3 to obtain coated steel members.
[0088] The obtained steel members were cut out and GDS (glow discharge optical emission spectrometry), SEM observation, and optical microscope observation were carried out in the manner described above to determine the decarburized layer depth and the internal oxide layer depth. Further, the obtained steel members were subjected to a tensile test, a bending test, and a spot welding test in the same manner as in Example 2, and the tensile strength, bendability, and weldability were evaluated. The results are shown in Tables 4-1 to 4-3.
[0089] [Table 4-1]
[0090] [Table 4-2]
[0091] [Table 4-3]
[0092] As shown in Tables 4-1 to 4-3, Examples D1 to D60, which satisfy the range of the present invention, have good results in terms of both structure and properties. However, Comparative Examples d1 to d23, which do not satisfy the range of the present invention, have chemical compositions and structures (depths of internal oxidation layer and decarburized layer) that are outside the range of the present invention, and at least one of bendability, weldability, and tensile strength does not satisfy the target. [Industrial Applicability]
[0093] According to the present invention, it is possible to obtain a high-strength steel member and steel plate having excellent crashworthiness. The steel member according to the present invention is particularly suitable for use as a frame part of an automobile. [Explanation of symbols]
[0094] 10 steel plate 11 Base steel plate 12 Scale 13 Decarburized layer 14 Internal oxide layer 110 Steel parts 111 Steel plate base material 112 scale 113 Decarburized layer 114 Internal oxide layer 210 Steel parts 211 Steel plate base material 213 Decarburized layer 214 Internal oxide layer 215 Covering
Claims
1. A steel sheet substrate; A coating containing Al and Fe formed on the surface of the steel plate substrate, The steel plate substrate comprises, in mass %, C: 0.10-0.65%, Si: 0.10-2.00%, Mn: 0.30-3.00%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, O: 0.010% or less, Ti: 0 to 0.100%, B: 0 to 0.0100%, Cr: 0-1.00%, Mo: 0-1.00%, Ni: 0 to 1.00%, Nb: 0 to 0.10%, Cu: 0 to 1.00%, V: 0-1.00%, Ca: 0-0.010%, Mg: 0 to 0.010%, Al: 0-1.00%, Sn: 0-1.00%, W: 0-1.00%, Sb: 0 to 1.00%, Zr: 0 to 1.00%, Co: 0 to 1.00%, and REM: 0-0.30%, and the balance being Fe and impurities, the steel plate substrate has a decarburized layer formed on the coating side, the decarburized layer has an internal oxidation layer formed on the coating side, The depth of the decarburized layer from the interface between the steel plate substrate and the coating is 30 μm or more; The depth of the internal oxide layer from the interface is less than 20 μm; No scale is present between the steel plate substrate and the coating containing Al and Fe.
1. A coated steel member comprising:
Citation Information
Patent Citations
Hot rolled steel sheet for hot press, method for producing the same, and method for producing hot pressed steel sheet member
JP2010043323A
High-strength press part and production method thereof
JP2015030890A
High strength hot-dip galvanized steel sheet and method of producing high strength hot-dip galvanized steel sheet
JP2017075394A
Method for manufacturing press hardened and coated steel parts at high production rates
JP2017518438A
High-strength plated steel sheet and method for producing same
WO2016111273A1